High-intensity exercise and recovery during short-term supplementation with creatine plus a protein-carbohydrate formula - Clark, JR (South African Journal of Sports Medicine, 2006)
Objective. To determine the effect of short-term creatine supplementation plus a protein-carbohydrate formula on high-intensity exercise performance and recovery. Design. A repeated-measures, experimental study, employing a randomised, double-blind, placebo-controlled, group comparison design was used. Interventions. Thirty active but not sprint-trained male subjects were randomly assigned to 1 of 3 groups: creatine plus protein-carbohydrate formula (CRF); creatine only (CRE); and control (CON). All groups were exposed to the same high-intensity sprint exercise programme, 3 times per week for 30 days. Main outcome measures. Dependant variables included total repeat sprint distance, fatigue index, perceived muscle pain, and blood lactate, urea, creatine kinase, and cortisol concentrations. Results. All groups significantly (p ≤ 0.05) increased total sprint distance and decreased blood urea concentrations. There were no significant changes in blood lactate or cortisol concentrations in any group. CRF showed significant decreases (p ≤ 0.05) in fatigue index, muscle pain, and creatine kinase concentration. However, no significant differences were found between groups. Conclusion. Short-term creatine supplementation with or without protein-carbohydrate supplementation does not appear to enhance performance or recovery significantly over high-intensity exercise training alone in non-sprint-trained individuals. A longer trial period may be required to evaluate effect on recovery more conclusively. In addition, the prime importance of physical conditioning, and in particular task-specific exercise training, in stimulating performance and recovery adaptations is highlighted. South African Journal of Sports Medicine Vol. 18 (4) 2006: pp. 136-140